PENGARUH PEMBERIAN JENIS FESES TERNAK BERBEDA TERHADAP PRODUKSI DAN NILAI GIZI RUMPUT BB BIOGEN - Rakhman, Abdul; Amrullah, Amrullah; Budiman, Cecep; Yani, Ahmad; Hamdani, Asrul; Wahyu Satria, Edi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Biogen BB grass is a feed crop with good quality to meet the needs of ruminant livestock. This study aims to determine the effect of providing different types of livestock feces on the production and nutritional value of Biogen BB grass. The study was conducted from January to March 2026 using a Randomized Block Design (RBD) with four treatments and four groups. Data analysis was performed through analysis of production and nutritional value using a Randomized Block Design (RBD). The results showed that all research variables, such as production and nutritional value of Biogen BB grass, had the highest average values in the P0 treatment with urea fertilizer at a dose of 280 grams per bed, with average fresh weight values ranging from 5,730-14,297 kg/m2, dry weight 3,197-7,145 kg/m2, dry matter 2,595-6,012 kg/m2, ash 0.297-0.606 kg/m2, crude fat 0.032-0.067, crude fiber 0.784-2,007 kg/m2, and crude protein 0.154-0.314 kg/m2.